2019
DOI: 10.1111/nep.13512
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcomes of patients switching from maintenance haemodialysis to peritoneal dialysis in Australia and New Zealand: Strengthening the argument for ‘peritoneal dialysis first’ policy

Abstract: Aims (1) To determine incidence and reasons for transfer from maintenance haemodialysis (HD) to peritoneal dialysis (PD); (2) To compare mortality of HD patients transferred to PD with those who initiated and remained on PD. Methods A 1:2 matched cohort of ANZDATA included patients dialyzing over 3 months dividing into 2 groups. Group A (HD to PD) was compared to group B (initiated and remained on PD) and matched PD group (Group C). We compared mortality by total time on dialysis regardless of modality. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…This review collected persons who underwent new dialysis from 1992 to 2018. In which, three sub‐cohorts by Chan et al, 26 Kotwal et al, 27,28 and Pianta et al 29 reported data in Sydney and the other reports 31,36,39–54 provided nationwide data. A study by Wang et al 32 was based on the CKD.QLD registry that collected data of a predialysis population in all public sector renal practises in Queensland since 2011.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This review collected persons who underwent new dialysis from 1992 to 2018. In which, three sub‐cohorts by Chan et al, 26 Kotwal et al, 27,28 and Pianta et al 29 reported data in Sydney and the other reports 31,36,39–54 provided nationwide data. A study by Wang et al 32 was based on the CKD.QLD registry that collected data of a predialysis population in all public sector renal practises in Queensland since 2011.…”
Section: Resultsmentioning
confidence: 99%
“…This review collected persons who underwent new dialysis from 1992 to 2018. In which, three sub-cohorts by Chan et al, 26 Kotwal et al, 27,28 and Pianta et al 29 reported data in Sydney and the other reports 31,36,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] provided nationwide data. A study by Wang et al 32 was based on the CKD.…”
Section: Characteristics Of Included Cohorts and Risk Of Biasmentioning
confidence: 99%
“…After a period on HD, most patients lose their residual renal function (RRF) and in these adequate solute clearances and ultrafiltration could be difficult to achieve with PD. Additionally, patients who transferred from HD to PD had a higher rate of peritonitis, PD technique failure, and death [43,44]. The association between AGR and patient's survival on HD needs to be explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Even if “peritoneal dialysis first” or “home haemodialysis first” probably represents a winning strategy for patients (more autonomy, more empowerment, better care), and for the health care system (lower costs of transportation, lower overall indirect costs and probably also lower costs of direct treatment, especially where PD is non assisted), this strategy is not uniformly developed, partly because of the fact that reimbursement is often lower and the advantage to the individuals and to society is not uniformly accompanied by an advantage to the dialysis providers [103,104,105,106,107].…”
Section: A Fundamental Question: Haemodialysis or Peritoneal Dialymentioning
confidence: 99%